Kyoto global consensus report on Helicobacter pylori gastritis and its impact on Chinese clinical practice. Issue 6 (June 2016) - Chen, Qi; Lu, Hong
Abstract: The Kyoto global consensus report on Helicobacter pylori ( H. pylori ) gastritis has had a great effect on the field of H. pylori studies worldwide. For the first time H. pylori gastritis was defined entirely as an infectious disease and H. pylori ‐associated dyspepsia as a new category of organic dyspepsia apart from functional dyspepsia, together with a proposed diagnostic algorithm. Accordingly, the report states that the eradication of H. pylori should be regarded as the first‐line treatment for dyspepsia. Moreover, H. pylori eradication before the development of pre‐neoplastic changes is recommended to reduce the risk of more serious complications of H. pylori gastritis. Despite the recommendations of this new global consensus, the task of transforming them into feasible and practical recommendations for individual countries will require them to become region‐specific, which requires further discussion.